China's Challenge to Liberal Norms The Durability of International Order - Jones, Catherine (Palgrave Macmillan UK, 2018)
Is China challenging liberal norms or being socialised to them? This book argues that China is incrementally pushing for re-interpretation of liberal norms, but, the result is that rather than being illiberal, this reinterpretation produces norms that are differently liberal and more akin to the liberal pluralism of the 1990s. In developing this argument, the author presents a novel way to understand and assess these incremental changes, and the causes of them. The book's empirical chapters explore China's views on norms of sovereignty and intervention, and aid and development, contrasting them against the current western liberal practices, but making the case that they are congruent with the attitudes understood as being broadly liberal-pluralist. This book will appeal to students seeking to understand how rising states may affect the current institutions of international order, and make assessments of how fast that order may change. It will also appeal to scholars working on China and institutions by aiding the development of new lines of enquiry. .